The Compliance Evaluation of Type-2 Diabetes Mellitus Patients Treating Therapy Diet Review from Theory of Planned Behavior - Sri Lestari Ramadhani Nasution; M. Ridho Fitra Alamsya; Ermi Girsang (Budapest International Research and Critics University, 2022)
Diabetes mellitus (DM) is a chronic condition that occurs when there is an increase in blood glucose levels because the body cannot produce insulin or use insulin effectively. This study aims to evaluate more in-depth information about compliance with Type-2 DM undergoing diet therapy from the perspective of the Theory of Planned Behavior. The informants in this study consisted of 17 informants consisting of 1 Doctor, 1 Nurse, and 15 Type 2 DM patients. This type of research was qualitative using in-depth interviews related to dietary compliance with Type 2 DM patients, then analyzed by triangulation. The results showed that diet-adherent behavior was significantly influenced by attitudes, subjective norms, individual behavior control, and intentions. The amount of intention and obedient attitude and behavior possessed by Type 2 DM patients will make it easier for Type 2 DM patients to carry out diet therapy. The level of adherence to diet therapy in this study with a high category of 10 patients with a percentage of 66.7%, patients with a level of adherence to diet therapy with a moderate category of 4 patients with a percentage of 26.7%, and patients with a level of adherence to diet therapy with a low category as many as 1 patient with a percentage of 6.7%. The amount of intention and obedient attitude and behavior possessed by Type 2 DM patients will make it easier for Type 2 DM patients to carry out diet therapy.